Sorsod Borsod . Hard Lines - Nagy, István (Kunt Ernő Képíró Műhely Egyesület, 2009)
Verzio FF Coming from completely different backgrounds, Peti and Robi might never have crossed each others' paths had they not become juvenile offenders and been sent to the same Juvenile Probation Supervision Office. Through their stories the film examines the effectiveness of a Western model of juvenile justice system in the socially highly divided Borsod County. Can an institution help where parenting has failed?